Perilaku Konsumen Pengguna Instagram di Era Marketing 4.0 - Luh Putu Indah Kencana Putri (Jurnal Manajemen dan Bisnis, 2019)
ABSTRACTThe study used a qualitative approach with a method of collecting data through in-depth interviews with 10 informants who were followers of the  @tubbeautystore  Instagram account. The purpose of this study is to explore the five stages of consumer behavior in the Marketing 4.0 era or what is called new customer path 5A. The results of this study indicate that informants obtained information through endorsers and also the activities of colleagues on Instagram until the informants were in the aware stage. All informants follow the @tubbeautystore Instagram account as an act of appeal. The informant wants to get information as soon as possible when there is information about the product needed (ask). Although currently digital development is very easy for activities, informants are still very comfortable to shop offline (act). Satisfied informants then recommend the TUB Beauty Store to other colleagues (advocate). Some informants do not go through all stages in customer path 5A. The conclusion of this study is that Instagram can help in the stage of awareness when companies use endorsers and hashtag services. When someone is interested they will take action following the account. After they are interested they tend to want to get information quickly. But even though the digital world allows all activities to be faster and easier, some are still convenient for shopping offline. And when satisfied, will undoubtedly recommend to others. The unique pattern of 5A consumer behavior is not always in the form of a serial.